2015
DOI: 10.1016/j.ijpara.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

First isolation of a new species of Leishmania responsible for human cutaneous leishmaniasis in Ghana and classification in the Leishmania enriettii complex

Abstract: An active case detection approach with PCR diagnosis was used in the Ho District of the Volta Region, Ghana that identified individuals with active cutaneous leishmaniasis. Three isolates were successfully cultured and DNA sequences from these were analysed (ribosomal RNA internal transcribed spacer 1; ribosomal protein L23a intergenic spacer; RNA polymerase II large subunit), showing them to be Leishmania, identical to each other but different from all other known Leishmania spp. Phylogenetic analysis showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
80
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 24 publications
1
80
0
1
Order By: Relevance
“…'siamensis', as a cause of human VL, predominantly in immunosuppressed patients [6770]. As discussed by other investigators [46], Leishmania 'siamensis' represents a nomen nudum , and is shown inverted commas here as a consequence. Leishmania 'siamensis' was detected in horses from the USA and central Europe [71, 72], and in Swiss cows [73].…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…'siamensis', as a cause of human VL, predominantly in immunosuppressed patients [6770]. As discussed by other investigators [46], Leishmania 'siamensis' represents a nomen nudum , and is shown inverted commas here as a consequence. Leishmania 'siamensis' was detected in horses from the USA and central Europe [71, 72], and in Swiss cows [73].…”
Section: Discussionmentioning
confidence: 83%
“…This led to the interpretation that a dixenous life cycle had evolved in the Leishmaniinae roughly 100 MYA in the Old World, and supported that Cretaceous reptiles were the first vertebrate hosts of the earliest dixenous Leishmaniinae [6, 8, 9]. However, this interpretation is not supported by current phylogenies that do not place the Sauroleishmania in a basal position or sister clade to all other Leishmania species [3, 4649] (Fig 8). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phylogenetic position of Sauroleishmania between the mammal-infecting subgenera Leishmania and Viannia 151617 suggests that it represents a widespread lineage of Leishmania that switched from mammals to reptiles as their main hosts. Sauroleishmania member L. tarentolae is a non-pathogenic lab model because it rapidly replicates in lizards.…”
mentioning
confidence: 99%